Meningococcal disease in travelers: update on vaccine options - Cramer, Jakob P.; Wilder-Smith, Annelies (Current opinion in infectious diseases, 2012)
Purpose of review: Invasive meningococcal disease is a rare but potentially devastating disease in travelers. In the past 5 years, significant progress in vaccine development has been made. The purpose of this review is to provide up-to-date information on the current status of risk of meningococcal disease in travelers and vaccine recommendations.Recent findings: More evidence on cases of meningococcal disease in travelers is now available. The main areas of highest risk for travelers continue to be the Hajj pilgrimage and travel to the meningitis belt. Two new tetravalent conjugate vaccines against serogroups A, C, W135 and Y have been licensed in North America, Europe and other countries. Significant progress has been made in the development of serogroup B vaccines. Summary: The vaccine of choice for travelers at risk of invasive meningococcal disease is a tetravalent conjugate meningococcal vaccine. Data on the need for re-vaccination schedules are still lacking, and so are data on immunogenicity in very young children and the elderly. The first vaccine against serogroup B may become available in early 2013 thus expanding the options of broadening the protection against more serogroups for travelers. Furthermore, the development of pentavalent vaccines will increase the uptake of meningococcal vaccines in the future.
Gesehen am 04.10.2018